STRUKTUR PASAR, DISTRIBUSI, DAN PEMBENTUKAN HARGA BERAS - Bhinadi, Ardito (Jurnal Ekonomi & Studi Pembangunan, 2012)
Abstract: Food commodities especially rice become one of the significant contributors to inflation. This paper aims to identify the market structure,  distribution patterns, and the formation of rice prices in Yogyakarta Indonesia. The method used is descriptive and statistical modeling approach Houck. Based on the results of the survey, it’s found that the market structure in Yogyakarta at the collectors is an oligopoly, the increasingly competitive downstream. The pattern of distribution of rice in Yogyakarta is following the path length, which is collected from the manufacturers. Wholesalers collectors bought new distributed to retailers for sale to consumers. At the level of manufacturers, the price of rice is determined by the buyer; collectors follow at the highest market price. At wholesalers levels, the price follows the price of competitors, and at the retailers, the price follows the highest market price. Factor that determines the price of rice from manufacturers to retailers is alike, that is the availability of supy. Abstrak: Komoditas pangan khususnya beras menjadi salah satu penyumbang inflasi yang signifikan. Paper ini bertujuan mengidentifikasi struktur pasar, pola distribusi, dan pembentukan harga beras di Yogyakarta. Metode yang dilakukan adalah statistik deskriptif dan pendekatan model Houck. Berdasarkan hasil survei ditemukan bahwa struktur pasar besar di Yogyakarta pada tingkat Pengepul  adalah oligopoli, semakin ke hilir semakin kompetitif.Pola distribusi beras di Yogyakarta mengikuti jalur panjang, yaitu dari Produsendikumpulkan Pengepul dibeli Pedagang Besar didistribusikan ke Pengecer baru dijual ke Konsumen. Pada tingkat Produsen, harga beras ditentukan oleh  pembeli; di tingkat Pengepul mengikuti harga pasar tertinggi. Di tingkat Pedagang Besar mengikuti harga pesaing, dan di tingkat Pengecer mengikuti harga pasar tertinggi. Faktor yang menentukan harga jual beras dari Produsen hingga Pengecer sama, yaitu ketersediaan pasokan.